Haemosporidian parasites in Antilophia galeata (Aves: Pipridae) in a Cerrado forest fragment (Bioscience Journal, 2023)
Haemosporidian parasites can cause pathogenic infections, leading to death or a reduction in the physical and reproductive abilities of the host. Several studies have identified haemosporidian infections in neotropical bird communities, but few have been conducted in populations, relating the infection to the biological attributes of the species. To determine haemosporidian prevalence in a population of Antilophia galeata and to assess factors that may be associated with parasitaemia, we analysed blood smears of 62 individuals from a Cerrado forest fragment. For each individual, the body mass, length of tarsus, sex, presence/absence of brood patch and feather moult were recorded. In total, 33 (53.2%) individuals were infected with haemosporidian parasites, 32 (51.6%) were infected with Plasmodium spp. and one (1.61%) was infected with Haemoproteus sp. Parasitaemia was not related to seasons, sex, reproduction, moulting or body condition but correlated positively with total leucocyte count, suggesting that individuals may be effective in infection control. This population may be tolerant to haemosporidian parasites because, despite the high prevalence, parasitaemia was low and constant; this is a potentially chronic infection that showed no adverse effects on the parameters analysed in this population.